Reflux symptom index and reflux finding score in 91 asymptomatic volunteers. (3rd July 2018) - Chen, Meixiang; Hou, Chenjie; Chen, Ting; Lin, Zhihui; Wang, Xin; Zeng, Yanling
Abstract: Background: The primary goal of this study was to investigating the symptoms, in addition to the reflux-related laryngopharynx inflammation performance of asymptomatic, volunteers, and verified the 'normal point'. Methods: A total of 91 asymptomatic subjects were recruited for this cross-sectional study between March 2016 and September 2016. Participants completed the reflux symptom index (RSI) assessment and underwent laryngostroboscopic examination using a rigid endoscope. Their RFS were graded according to the laryngeal findings. The distribution and the relationship of the RSI and the RFS were analyzed. Results: The mean RSI of individuals was 2.24 ± 2.34 [95% confidence interval (CI) = 1.75, 2.72], and the mean RFS of individuals was 5.78 ± 1.74 (95% CI = 5.42, 6.15). The Pearson product–moment correlation coefficient of the RSI and RFS scores was –0.084 ( n  = 91, p  = .428). Conclusions: Asymptomatic people could present relatively high RFS scores, and no linear relationship existed between RSI and RFS.